2015
DOI: 10.1021/acsmedchemlett.5b00001
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Clinical Candidate BMS-906024: A Potent Pan-Notch Inhibitor for the Treatment of Leukemia and Solid Tumors

Abstract: Structure−activity relationships in a series of (2-oxo-1,4-benzodiazepin-3-yl)-succinamides identified highly potent inhibitors of γ-secretase mediated signaling of Notch1/2/3/4 receptors. On the basis of its robust in vivo efficacy at tolerated doses in Notch driven leukemia and solid tumor xenograft models, 12 (BMS-906024) was selected as a candidate for clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 12 publications
1
49
0
Order By: Relevance
“…It was previously reported that BMS-906024 potently inhibits the activation of all four Notch receptors (20). To determine the optimal concentration of BMS-906024 that inhibits the presenilin gamma secretase complex in NSCLC, we measured activated Notch1 ICD protein levels.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It was previously reported that BMS-906024 potently inhibits the activation of all four Notch receptors (20). To determine the optimal concentration of BMS-906024 that inhibits the presenilin gamma secretase complex in NSCLC, we measured activated Notch1 ICD protein levels.…”
Section: Resultsmentioning
confidence: 97%
“…BMS-906024 demonstrated a low nanomolar half maximal concentration (IC 50 ) in in vitro enzyme assays and cellular Notch reporter assays (20, 21). Oral administration of BMS-906024 in mice bearing T-ALL or breast cancer xenografts resulted in dose-dependent inhibition of tumor growth, with no overt toxicity observed in dosages up to 6 mg/kg (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For BMS-906024, the accuracy was mostly within 85 to 115% in QC samples containing up to ∼30% of hemolyzed blood, with a slight trend toward decreasing accuracy starting from 20% of hemolyzed blood. Nevertheless, it met the acceptance criteria based on the Bioanalytical Guidance from US FDA and EU EMA guideline (18,26). The same trends were observed for BMS-911557.…”
Section: Effect Of Hemolysis On the Internal Standard Responses Accumentioning
confidence: 52%
“…BMS-906024 (Fig. 1a) is currently being developed for treatment of cancer (26), and BMS-911557 is its metabolite (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%